Psychological Hardiness and its Relationship with Life Satisfaction for sample of breast cancer patients Afield Study in Lattakia governorate (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aimed to know the relationship between Psychological Hardiness and the life satisfaction and realized the level of Psychological Hardiness and the level of life satisfaction for sample of breast cancer patients, also aimed to examine the differences in Psychological Hardiness and life satisfaction according to the variables (age, marital status, duration of the disease). The research used Descriptive analytical method, The sample included (112) breast cancer patients in the year 2017. The research used two measures for Psychological Hardiness and the life satisfaction. Validity of the questionnaire was established though a jury of (7) of the teaching staff at Tishreen University. Pilot sample consisted of (28) breast cancer patients. Reliability was established by Cronbach – Alpha Reliability at lest (0.835) for life satisfaction measure, and (0.867) for Psychological Hardiness measure. The final results showed there are positive relationship between Psychological Hardiness and the life satisfaction for the Students. In fact, the level of Psychological Hardiness and life satisfaction for breast cancer patients were middle rated for the sample research. Finally, the study showed significant differences in Psychological Hardiness to the variable age in favor of the more than (45) years, also to marital status in favor of the marries, and to duration of the disease in favor of the breast cancer patients more than (5) years, also there are showed significant differences in the level of life satisfaction according to the variable age in favor of the more than (45) years, also to marital status in favor of the marries, and to duration of the disease in favor of the breast cancer patients more than (5) years.